The Right Protection of Indigenous People in the Spatial Planning Policy During the Regional Autonomy Era of North Halmahera Regency in North Maluku Province - Salha Marsaoly; Siti Barora; Mulyadi Tutupoho (Faculty of Law, Khairun University, 2018)
The recognition and respect for the indigenous people along with their traditional rights is affirmed on the article 18B verse (2) of the 1945 Constitution of the Republic of Indonesia; that includes the indigenous people of Hibualamo in North Halmahera regency. The spatial planning contect requires the involvement of the indigenous people to achive a balance between development and tenure rights so that it will be in line with the local wisdom to support sustainable development.